2021
DOI: 10.26444/aaem/133896
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19 – Possible interrelations with respiratory comorbidities caused by occupational exposure to various hazardous bioaerosols. Part II. Clinical course, diagnostics, treatment and prevention

Abstract: Introduction and objective. The course of COVID-19 caused by the SARS-CoV-2 may be aggravated by bioaerosols containing other viruses, bacteria, and fungi, occurring mainly in the occupational environment. Hence, the diagnostics and treatment of COVID-19 should address such a possibility in the anamnesis, treatment and final recommendations for avoiding of adverse exposure. Abbreviated description of the state of knowledge. As SARS-CoV-2 attacks primarily the respiratory system and the severe manifestation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Thus, no relevant studies are included in this review effort. a The lists were compiled primarily from [43,51,54,59,76,87,152,158,159,184]. Several publications in Table 5 (e.g., [174,178]) used selective agar media to identify and quantify certain microorganisms.…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, no relevant studies are included in this review effort. a The lists were compiled primarily from [43,51,54,59,76,87,152,158,159,184]. Several publications in Table 5 (e.g., [174,178]) used selective agar media to identify and quantify certain microorganisms.…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
“…Sampling represents the collection of airborne microbes (more strictly speaking, microbe-laden particles), cultivation involves the growth of target microbes on a growth medium or media to form visible colonies, and enumeration refers to the counting of formed bacterial or fungal colonies [295]. An optional step is identification, with aims to determine microbial species based on the appearance of the colonies formed [43,51,158,159,193]. Identification can also be conducted by taking individual colonies for further investigation including microscopic analysis, biochemical testing, DNA sequencing, and proteomic analysis [59,101,173,183,192].…”
Section: Bioaerosol Characterization 441 Bacterial and Fungal Counts ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Workers' skin microbiota may be easily disturbed by environmental microbes through direct contact with animals, bedding materials, feeding facilities, and especially airborne microbial communities [ 2 , 3 , 4 ]. It has been reported that the air of livestock farms, especially swine farms, is full of a large amount of dust, bacteria and fungi [ 5 , 6 ], the concentration of bacteria in the air can reach 2 × 10 7 [ 7 ], which is twice the level usually measured in indoor air. In addition, animal husbandry generally requires higher health standards to minimize economic losses caused by infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that some micronutrient supplements may also help the immune system of a COVID-19 patient to maintain integrity. Due to their immunomodulatory effects, essential micronutrient supplements [11,12,13,14,15], e.g., zinc, have recently received critical examination. Zinc is a micronutrient critical for the growth, development, and maintenance of immune barriers, such as the skin and mucous membranes.…”
Section: Introduction and Objectivementioning
confidence: 99%